ANALISIS EMPIRIS EFEKTIVITAS MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA MELALUI JALUR EKSPEKTASI INFLASI PERIODE 1990:2-2007:1 - M. Natsir Natsir (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
This study used Vector Auto regression (VAR) model to analyze effectiveness of monetary policy transmission mechanism in Indonesia through Inflation Expectation Channel period 1990:2-2007:1. That effectiveness was measured by two indicators, they are: (1) : (1) how fast or how many time lag needed since the shock of monetary instruments (rSBI) until the realisation of final target of monetary policy (inflation). (2) How strong the variables of inflation expectation line response the shock of SBI interest rate and other variable. This study used secondary data issued by Bank Indonesia and BPS as well as from International Finance Statistic (IFS). The result of the study shows that response velocity of variable in Inflation Expectation Channel towards shock instrument of monetary policy (rSBI) until reach the final target or time tag about 12 quarterly or twenty six months. While impulse response function of variables in this channel to the shock instrument of monetary policy (rSBI) is quiet weak and the main channel that is inflation expectation and exchange rate are not able to explain diversity final target of monetary policy (inflation) about 33,88%, while variable of inflation expectation only able to explain diversity of inflation about 15,03%. Meanwhile, we still able economically to conclude that mechanism of monetary policy transmission through Inflation Expectation Channel is effective to reach the final target of monetary policy of Indonesia period of 1990:2-2007:1